Current Murine Models and New Developments in H3K27M Diffuse Midline Gliomas - Welby, John P.; Kaptzan, Tatiana; Wohl, Anton; Peterson, Timothy E.; Raghunathan, Aditya; Brown, Desmond A.; Gupta, Shiv K.; Zhang, Liang; Daniels, David J. (Frontiers in Oncology, 2019)
Diffuse Midline Gliomas with H3K27M mutation constitute the majority of Diffuse Intrinsic Pontine Glioma (DIPG), which is the most aggressive form of pediatric glioma with a dire prognosis. DIPG are lethal tumors found in younger children with a median survival less than one year from diagnosis. Discovery of the characteristic Histone 3-Lysine-27-Methionine (H3K27M) mutations offers opportunity and hope for development of targeted therapies for this deadly disease. The H3K27M mutation through epigenetic alterations in specific H3 lysine trimethylation levels and subsequent gene expression plays a significant role in pathogenesis of DIPG. Animal models accurately depicting molecular characteristics of H3K27M DIPG are important to elucidate underlying pathologic events and for preclinical drug evaluation. Here we review the past and present DIPG models and describe a newly developed patient-derived DIPG model, PED17. The PED17 cells retain characteristic genomic and phenotypic hallmarks of DIPG and established orthotopic tumors in the mouse brainstem that recapitulate radiographic and morphological features of the original human DIPG tumor. These new models that contain the H3K27M mutation constitute a valuable tool to evaluate novel therapeutic approaches for this devastating disease.